(untitled) (Journal of Fiber Bioengineering and Informatics, 2026)
This study is to address the lack of targeted research on accessible clothing for the visually impaired. In response to this gap, we conducted a mixed-methods study involving in-depth interviews, questionnaire surveys, real-world experiments with visually impaired participants to examine their specific clothing needs during meals, and Market investigation. Based on the analysis of over 70 sample cases, the main challenges were identified as color recognition, stain detection, garment cleaning, functional design, and personalization. Meanwhile, we identify core design requirements for accessible bibs, including stain-resistant materials, ergonomic structures, and aesthetic considerations tailored to users preferences. This paper contributes empirical insights and practical guidelines to support inclusive design in sustainable fashion, offering a theoretical foundation for future development of accessible clothing for the visually impaired.